2011
DOI: 10.4103/2045-8932.87308
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic and Heritable PAH Perturb Common Molecular Pathways, Correlated with Increased MSX1 Expression

Abstract: The majority of pulmonary arterial hypertension (PAH) is not associated with BMPR2 mutation, and major risk factors for idiopathic PAH are not known. The objective of this study was to identify a gene expression signature for IPAH. To accomplish this, we used Affymetrix arrays to probe expression levels in 86 patient samples, including 22 healthy controls, 20 IPAH patients, 20 heritable PAH patients (HPAH), and 24 BMPR2 mutation carriers that were as yet unaffected (UMC). Culturing the patient cells removes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 44 publications
2
40
1
Order By: Relevance
“…This may be because the previous study used a smaller sample size (three patients and four control subjects) or because of some fundamental difference between NMD2 and NMD1 patients. We have also recently published a study concentrating on identifying risk factors in patients with idiopathic PAH (36). Because of its design, carriers and noncarriers with BMPR2 mutations were not well separated, but in that study patients with idiopathic and heritable PAH were distinguished by alterations in gene expression related to metabolism and oxidative stress, in agreement with the current study's assessment of metabolism as a central risk factor for development of PAH.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This may be because the previous study used a smaller sample size (three patients and four control subjects) or because of some fundamental difference between NMD2 and NMD1 patients. We have also recently published a study concentrating on identifying risk factors in patients with idiopathic PAH (36). Because of its design, carriers and noncarriers with BMPR2 mutations were not well separated, but in that study patients with idiopathic and heritable PAH were distinguished by alterations in gene expression related to metabolism and oxidative stress, in agreement with the current study's assessment of metabolism as a central risk factor for development of PAH.…”
Section: Discussionsupporting
confidence: 59%
“…First, it may just be a matter of degree: On a cellular level, patients with PAH may produce more ROS than carriers, who produce more than healthy control subjects. However, the difference may also lie in the ability to adapt to oxidative stress or the metabolic problems that underlie it, either directly through increased activity of systems that counteract oxidative stress (e.g., we have recently shown increased metallothioneins in carriers) or indirectly through increased function of salvage pathways in energy metabolism (36). Our data cannot distinguish between the molecular mechanisms behind this observed increase in ROS production.…”
Section: Discussioncontrasting
confidence: 47%
“…We found 409 probe sets representing 279 unique Entrez IDs with average differences of at least twofold between controls and either HPAH or IPAH samples (see Supplemental Table S8). Analysis of statistically overrepresented gene ontology groups showed that pathways differentially regulated in fibroblast lines were, for the most part, similar to pathways we previously reported to be dysregulated in cultured patient lymphocytes (5). These included 134 of the 279 genes related to altered metabolism, 25 cell adhesion genes [P ϭ 0.013 for overrepresentation of gene ontology group, by hypergeometric test, with Benjamini and Hochberg (6) multiple comparisons adjustment], 16 circulatory system process genes (P ϭ 0.0002), and 34 chemical stimulus response genes (P ϭ 0.022), including 10 oxygen-level response genes (P ϭ 0.008).…”
Section: Pah-dependent Changes In the Wnt Pathway Are A Function Of Dmentioning
confidence: 88%
“…Wnt pathway signal, aside from increased TCF expression, was not apparent in any of the studies relying on fresh or cultured peripheral blood mononuclear cells (PBMC). On the basis of our own published arrays, this is likely because cell-specific Wnt pathway components are not significantly altered in PBMC (5,65). Thus PBMC are likely not the ideal candidate cell type relative to adherent/polar vascular cells in which to assay this pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation